The association of six-minutes walking test (6MWT) with cardiovascular disease risk among older women with type 2 diabetes mellitus in a rural primary health care: a pilot observational study - Rakhmat Ari Wibowo; Arum Tri Wahyuningsih; Rio Jati Kusuma; Wahyu Pamungkasih; Denny Agustiningsih (Journal of Community Empowerment for Health, 2020)
The recent systematic review found that cardiovascular events contributed to approximately half of all deaths among patients with type 2 diabetes mellitus (T2DM). Several studies suggested that the six-minutes walking test (6MWT) could be a valuable prognostic tool for predicting cardiovascular disease (CVD) events in particular diseases. However, less is known concerning the role of 6MWT in predicting CVD events among patients with T2DM. Thus, this pilot observational study aimed to test the feasibility of conducting the 6MWT and to examine the association of measures collected during 6MWT with ASCVD risk estimator parameters for predicting CVD events among T2DM patients. Fourteen older women with T2DM in a rural primary health care were enrolled in this cross-sectional study. Blood pressure measurement, heart rate measurement, and blood sampling for HDL, LDL, and total cholesterol measurements were carried out during rest. Both heart rate and distance were measured at the end of the following 6MWT. Feasibility data were collected. Recruitment rate and measurement completion rate were 85.7% and 40% respectively. No adverse events during the 6MWT were reported. Patient’s heart rate at the end of 6MWT was correlated with diastolic blood pressure (r=0.5 p=0.48). Multivariate analyses suggested that every one-meter increase in distance of 6MWT, there is a decrease in diastolic blood pressure of -0.9 mmHg (p=0.01; 95% CI= -1.6 to -0.2). In conclusion, 6MWT is a feasible simple test which could provide a valuable prediction of ASCVD risk among older women with T2DM. Thus, this test should be considered to be conducted as a part of routine examination. Cohort study with a larger sample could be suggested to establish the usefulness of the 6MWT in predicting CVD risk.